Analysis of the Effectiveness of Earmarking Tax Policies for Street Lighting Taxes as an Effort to Provide Street Lighting in the Province of the Special Capital Region of Jakarta in 2018-2020 - Mainita Hidayati Keman; Robby Irvawan; Dodi Rahmat Setiawan; Farahdiba Rizqi Rizqi (Ilomata International Journal of Tax and Accounting, 2022)
The earmarking tax policy on street lighting tax is a policy of allocating funds from lighting tax revenues for the provision of public street lighting (PJU). The phenomenon in this study is the lack of number of PJU lamps in DKI Jakarta Province and delays in payment of electricity bills for PJU lamps due to budget refocusing to deal with the Covid-19 outbreak in Indonesia. The purpose of this study is to analyze the effectiveness of the earmarking tax policy on street lighting tax as an effort to provide street lighting in DKI Jakarta Province in 2018-2020, as well as obstacles and efforts related to the earmarking tax policy on street lighting tax. This study uses a descriptive qualitative approach. The results of this study indicate the effectiveness of the earmarking tax policy on street lighting tax in DKI Jakarta Province in 2018-2020, based on Riant Nugroho's theory of effectiveness, namely the right policy, right implementation, right target, right environment, and right process has been running well and effectively. However, for society, the right target for installing PJU lamps is considered not effective enough where there are still unequal distribution of PJU lamps in DKI Jakarta Province. Then, based on the effectiveness of the allocation of street lighting tax funds for the provision of street lighting in 2018-2019, it is said to be effective where the allocation of these funds has exceeded 90%. However, in 2020 it is said to be ineffective because the allocation of these funds only reached 36%.